Not all that shines is cancer: pulmonary cryptococcosis mimicking lymphoma in [(18)] F fluoro-2-deoxy-D-glucose positron emission tomography - Hamerschlak,Nelson (2012)
We report of a case of pulmonary cryptococcosis mimicking lymphoma in a positron emission tomography (FDG-PET) scan. A 62-year old man with diffuse large B-cell lymphoma had complete resolution of abdominal and pulmonary lesions after three cycles of rituximab-based chemotherapy (R-CHOP). However, FDG-PET showed new pulmonary nodules, suggesting active lymphoma. Chronic inflammatory granuloma was seen in the histopathological exam, with round-shaped structures compatible with fungus, later identified as Cryptococcus neoformans on culture. The lesions disappeared after 6 weeks of fluconazole therapy, and the patient could continue chemotherapy without further infectious complications.